1992
DOI: 10.1001/archsurg.1992.01420040058010
|View full text |Cite
|
Sign up to set email alerts
|

Mesh Tube—Constricted Varicose Veins Used as Bypass Grafts for Infrainguinal Arterial Reconstruction

Abstract: Varicose veins are generally deemed inappropriate graft material for arterial reconstructions despite their physiologic flow surface because of their large and irregular caliber. Size reduction by threading such veins in constricting tubes may create bypass grafts of suitable caliber as long as redundant wall material does not cause stenoses. Sixteen human varicose veins (mean +/- SD, 13 +/- 3 mm diameter) obtained after stripping operations were inserted into Dacron mesh tubes of 6 mm internal diameter. Paraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Berkowitz and O'Neill 6 described good results using reinforced vein grafts for renovascular reconstruction in children. Moritz et al 7 reported successful infrainguinal arterial reconstruction after external reinforcement of both cephalic veins and varicose veins obtained by stripping. Follow-up in our patients confirmed excellent long-term outcome using reinforced varicose saphenous vein grafts for femoropopliteal bypass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Berkowitz and O'Neill 6 described good results using reinforced vein grafts for renovascular reconstruction in children. Moritz et al 7 reported successful infrainguinal arterial reconstruction after external reinforcement of both cephalic veins and varicose veins obtained by stripping. Follow-up in our patients confirmed excellent long-term outcome using reinforced varicose saphenous vein grafts for femoropopliteal bypass.…”
Section: Discussionmentioning
confidence: 99%
“…This improvement has been attributed to a decrease in shear stress on the vascular wall. 7,9 Prosthetic reinforcement may be applied to all or part of the vein graft depending on the extent of varicose dilatation. Anastomosis should not be covered to avoid a compliance mismatch between the vein graft and artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An external support has been proposed to increase the use of large diameter veins that are otherwise considered unacceptable for arterial replacement. Clinical studies have shown acceptable results utilizing varicose vein grafts with prosthetic reinforcement [15].…”
Section: Introductionmentioning
confidence: 99%
“…External synthetic stents or sheaths have been used to taper vein grafts clinically or to reduce intimal hyperplasia caused by the arterialization process. 17 Jeremy et al 18 showed that external synthetic stents inhibit neointima formation and promote angiogenesis in vein grafts. They also prevent thickening of vein grafts and by this possibly prevent late failure.…”
Section: Discussionmentioning
confidence: 99%